Chronic sorrow in mothers of adult children with cerebral palsy: an exploratory study - Masterson, Marilyn K. (Kansas State University, 2010)
Chronic sorrow has been defined as a permanent and reoccurring experience of pervasive sadness and loss which underlies the life experience and which recurs over time for the parent of a child with developmental, medical, or behavior issues that prevent him from participating in society in a way previously anticipated by parents. The functional question asked of the mothers was: “Some parents have described a sadness that can occur when they think about their child with a disability. Parents can believe they are functioning well, but have times where they feel the loss for their child.” To date, little research has targeted chronic sorrow among parents of adult children who have a disability. Neither is it known how chronic sorrow exists and has changed over the years since the initial diagnosis for this specific sample. This exploratory, qualitative study focused specifically on mothers of adult children with cerebral palsy. Snowball sampling was utilized to recruit six mothers in northeastern Kansas who were primary caregivers to their adult children with CP. Data were gathered with face-to-face mixed self-report surveys, including the Kendall Questionnaire on Chronic Sorrow; two surveys which assessed demographic, potential complications from cerebral palsy, and available resources; and a standard schedule open-ended interview targeting: personal experiences of chronic sorrow, chronic sorrow triggers (developmental milestones), and losses (including support, roles and responsibilities, and quality of life). Two-coder analyses of interview responses were conducted within cases and comparisons were made across cases. Common themes identified in the narratives included sense of isolation, fear for the future, frustration, loss of hope, exhaustion, sadness, financial challenges, guilt, and anger. For example, isolation was another theme that changed over time depending on if the mothers were providing full-time care. Also, fear for the future was a universal theme when the children were much younger, but it changed into loss of hope for some of the mothers when the child was the age of an adult. The relevance of the findings was discussed, with particular focus being the subjective meanings of chronic sorrow for this sample. Recommendations for advancing research, practice, and policy are offered.
Keywords: Chronic sorrow; Cerebral palsy; Mothers; Adult children; Loss; Health Sciences, Nursing (0569); Psychology, Developmental (0620); Sociology, Individual and Family Studies (0628)